Effects of silica fume type and cementitious material content on the adiabatic temperature rise behavior of LHP cement concrete. (10th October 2022) - Wang, Qinghe; Liu, Ruixin; Liu, Changyong; Liu, Puyuan; Sun, Liye
Highlights: The adiabatic temperature rise test of LHP concrete. Effects of silica fume on adiabatic temperature rise behavior of LHP cement concrete. The prediction model of adiabatic temperature rise behavior of LHP cement concrete. Abstract: In mass concrete, low-heat Portland (LHP) cement is widely used, which calls for a systematic study of LHP cement concrete's adiabatic temperature rise behaviors to improve temperature control in the early stages of concrete. Herein, the impacts of two kinds of silica fume (purity: 94.97 % and 97.28 %) and three cementitious material contents (445, 475, and 500 kg/m 3 ) on the adiabatic temperature rise and other thermal and mechanical performances of LHP cement concrete were investigated. The correlation between experimental parameters and LHP cement concrete's adiabatic temperature rise was quantified, and a corresponding model suitable for this type of concrete was obtained. The results illustrated that silica fume type had a limited influence on the LHP cement concrete's adiabatic temperature rise performance, with a maximum difference of only 1.88 %. By comparison, the effects of cementitious material content were more significant. When the cementitious material content was decreased from 500 kg/m 3 to 445 kg/m 3, the concrete's final temperature could be reduced by 10.95 %. In addition, while the effects of silica fume type and cementitious material content on the thermal and mechanical properties of LHP cement concrete were found to be limited, the addition of high purity silica fume caused a more significant enhancement in the mechanical performance of LHP cement concrete. Compared with concrete containing 500 kg/m 3 cementitious material, the thermal conductivity and thermal diffusivity of concrete of 445 kg/m 3 were shown to increase by 12.53 % and 7.92 %, respectively. Moreover, the composite exponential adiabatic temperature rise model achieved higher accuracy than the hyperbolic model and was found reliable to be adopted to predict LHP cement concrete's adiabatic temperature rise.